2005
DOI: 10.1002/adma.200400672
|View full text |Cite
|
Sign up to set email alerts
|

Biomorphic Cellular SiSiC/Zeolite Ceramic Composites: From Rattan Palm to Bioinspired Structured Monoliths for Catalysis and Sorption

Abstract: The density of stacking faults was estimated following the Warren method [30]. For the (10.1) line, and taking into account only the stacking faults of growth type, d is given bywhere d is the reticular distance corresponding to the (10.1) reflection and c is the cell parameter of the hexagonal phase [30]. B c (2h) is the FWHH corrected for broadening due to the finite size of the crystallites, according to the relationScanning electron microscopy (SEM) observations were carried out with a Hitachi 4500 field e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…By impregnating the carbon preforms with alkoxide solutions and applying standard sol-gel chemistry, various metal oxide macroporous ceramics have been produced using this approach. SiC-based cellular ceramics of diverse compositions were fabricated by Greil and colleagues 52,[55][56][57] via the infiltration and reaction of liquid or gaseous silicon metal with the carbon preform. Other gaseous metals and metal precursors, [58][59][60] preceramic polymers, 63 ceramic suspensions, 62 and salt solutions 64,65 have recently been employed to infiltrate the carbon cellular structure and obtain oxide, carbide, phosphate, and zeolite-containing macroporous ceramics through the wood-derived replica technique.…”
Section: Replica Techniquementioning
confidence: 99%
“…By impregnating the carbon preforms with alkoxide solutions and applying standard sol-gel chemistry, various metal oxide macroporous ceramics have been produced using this approach. SiC-based cellular ceramics of diverse compositions were fabricated by Greil and colleagues 52,[55][56][57] via the infiltration and reaction of liquid or gaseous silicon metal with the carbon preform. Other gaseous metals and metal precursors, [58][59][60] preceramic polymers, 63 ceramic suspensions, 62 and salt solutions 64,65 have recently been employed to infiltrate the carbon cellular structure and obtain oxide, carbide, phosphate, and zeolite-containing macroporous ceramics through the wood-derived replica technique.…”
Section: Replica Techniquementioning
confidence: 99%
“…For example, the high permeability and enhanced surface area of the hierarchical porous systems shown in Fig. 2.3a-c have been considered for catalytic and gas adsorption applications that require high density of reactive sites combined with fast mass transport (Zampieri et al 2005;Vakifahmetoglu et al 2010). In this case, enhanced fluid transport can be achieved with large macropores, while the high density of reactive sites arises from the pores at smaller length scales.…”
Section: Synthetic Hierarchically Porous Materialsmentioning
confidence: 98%
“…For instance, it has been found that the high surface area and elongated nature of the porosity makes bioSiCp an interesting catalyst carrier, especially for high temperature reactions such as partial oxidation of methane to syngas [106], cellulose conversion to hydrogen [107] using Ni particles, or catalytic combustion of hydrogen [108] but also combined with zeolites to form structured monoliths for sorption and catalysis [109,110].…”
Section: Applicationsmentioning
confidence: 99%